2010
DOI: 10.1136/vr.c4901
|View full text |Cite
|
Sign up to set email alerts
|

Severe generalised alopecia associated with demodicosis in a roe deer

Abstract: Practitioners should be aware of demodicosis as a differential diagnosis for alopecia in roe deer. We would be interested to hear of any similar observations in wild deer species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…By contrast, other authors have apparently not observed alopecia to the same extent as we have, although demodectic mange has been previously reported [90,91]. In our study, alopecia was often associated either with biting lice infestation or else the etiology was unclear.…”
Section: Discussioncontrasting
confidence: 91%
“…By contrast, other authors have apparently not observed alopecia to the same extent as we have, although demodectic mange has been previously reported [90,91]. In our study, alopecia was often associated either with biting lice infestation or else the etiology was unclear.…”
Section: Discussioncontrasting
confidence: 91%
“…Strugnell and others (2010) reported the first case of demodicosis with alopecia in roe deer in Great Britain. This was a single case from North Yorkshire.…”
Section: Figurementioning
confidence: 99%